The Effect of Giving Jagaq Porridge on Body Weight and Height of Stunted Toddlers Aged 12-24 Months in the Work Area of the Depar Health Center - Ririn Noviani Dewi; Umi Kalsum; Nursyahid Siregar (Formosa Journal of Science and Technology, 2023)
This study aims to determine the effect of giving jagaq porridge on the body weight and height of stunted toddlers aged 12-24 months. This type of research is a quantitative research with a quasi-experimental research design with a one group pre-post test design. The population in this study were 11 stunted toddlers aged 12-24 months who were at the Dempar Health Center in 2022. The sampling technique used was total sampling. Data analysis technique using paired t-test. Based on the research results obtained, it can be concluded that there is an effect of giving jagaq porridge on body weight (p-value = 0.003) and height (p-value = 0.000) of stunted toddlers aged 12-24 months.